Foil fatigue sensor for «Structural Health Monitoring» systems - Карускевич, М. В.; Корчук, О. Ю.; Лісовська, М. В. (Proceedings of National Aviation University (archive), 2013)
The concept of foil fatigue sensor is presented. The deformation relief of the sensor surface is considered as an indicator of the fatigue damage. The quantitative parameter of the deformation relief intensity determined by the computer aided method is applied.   The possibility to monitor fatigue damage of metal structures by the application of foil fatigue sensor is proved. The method  to control sensitivity of the sensors is shown